Geoscience of Climate and Energy 6. Tree Rings as Temperature Proxies - Luckman, Brian H. (Geoscience Canada, 2010)
Tree rings have provided annually resolved and precisely dated proxy climate records for large areas of the earth’s land surface. These records are considerably longer than instrumental climate data and allow the reconstruction of climate history, trends and patterns over a wide range of temporal and spatial scales. This paper briefly reviews the principles and assumptions that underlie the reconstruction of temperatures from tree-ring data, and provides three examples of their application at differing spatial and temporal scales over the last millennium. SOMMAIRE Les anneaux de croissance des arbres ont permis d’expliquer et de dater avec précision, bien qu’indirectement, des événements climatiques portant sur de grandes étendues de la surface terrestre. La portée temporelle de ces archives naturelles dépasse de beau-coup celle de tout registre climatique d’instruments humains et permet de reconstituer l’histoire, les tendances et patrons climatiques pour une gamme étendue d’échelles dans le temps et l’e-space. Le présent article présente une revue sommaire des principes et postulats qui fondent la reconstitution des conditions météorologiques à partir des données des anneaux de croissance des arbres, ainsi que trois exemples d’application pour différentes échelles temporelles et spatiales au cours du dernier millénaire.